Developing transitional justice for youth: an assessment of youth reintegration programmes in Colombia - Mitra, Arpita (International journal of transitional justice, 2022)
Young people, or ‘youth’ are one of the key groups affected by armed conflict as well as in the process of transitioning from it. This article explores what a youth-inclusive process of transitional justice may entail. It looks at the reintegration of youth, who were previously associated with armed groups, into civilian lives through Disarmament, Demobilisation and Reintegration (DDR) programmes and broader community-based initiatives with a prevention focus that lie outside a traditional transitional justice framework. The article scopes the study to the context in Colombia. A selection of programmes is assessed alongside international standards on youth reintegration, particularly the UN Integrated DDR Standards on Youth and complemented with empirical evidence that attests the ways in which youth experience these interventions. In doing so, the article analyzes potential ‘blueprints’ for the programmatic response to youth reintegration and contribute to an under-researched area that links youth, transitional justice and guarantees of non-recurrence.